Does Motor Manual Pine Oleoresin Tapping Bring Work-Related Musculoskeletal Disorders Risk to the Tappers? (RoM, REBA, RULA, and OWAS Based Postural Analysis) - Efi Yuliati Yovi; Bayu Wilantara (Department of Forestry, Faculty of Agriculture, University of Lampung, 2023)
Rosin and turpentine oil are commercially developed non-timber forest products generated from pine oleoresin. In Indonesia, the Quarre method is utilized to tap manually or motor-manually (using handheld tapping machines). Handheld tapping machines can greatly boost productivity on the work, but they may also pose serious risks to workers’ health. This study aimed to examine the work-related musculoskeletal disorders (WMSDs) risk of motor-manual tapping by using four postural analysis instruments: Natural Range of Motion (RoM), Rapid Entire Body Assessment (REBA), Rapid Upper Limb Assessment (RULA), and the Ovako Working Posture Analyzing System (OWAS). In addition to the finding that the use of handheld machines is associated with a high WMSDs risk level, particularly in the work element of renewing the tapping faces, this study demonstrated that RULA is a postural-based risk level instrument with the highest level of sensitivity when being used to assess risk levels in tapping activities involving a great deal of upper limb movements. Despite the widespread use of OWAS for emergency corrective action, this study demonstrates that OWAS has a very low level of sensitivity. For this reason, we stress the importance of using a wide range of instruments for risk assessment to get more accurate results. Keywords: Musculoskeletal disorders, pine tapping, postural analysis, risk level